Pembelajaran Berbasis Multiple Intelligences dan Problem Based Learning untuk Meningkatkan Kreativitas Mahasiswa - Karmila, Nita (Universitas Djuanda, 2020)
The purpose of this study is to increase student learning creativity in school-based management courses through learning based on multiple intelligences and problem-based learning. The research method used was quantitative, quasi-three-class experiment with the research subjects of PGSD students, FKIP Pakuan University even semester who took school-based management courses. Two classes were given treatment with two different lessons, namely learning based on multiple intelligences and problem-based learning, while one class was the control class. Observations and assessments are carried out on the cognitive aspects of students. Based on the results of hypothesis testing, the results of the study can be concluded that there is no difference in creativity with the use of multiple intelligence models, problem based learning and conventional models. From the t-test calculation, the t-count is smaller than t (table.) However, if it is seen from the N-Gain acquisition in each model, the biggest model in a row is the Problem Based learning model with N-Gain 62. Followed by N-gain conventional class, namely 35. Finally, the N-gain class Multiple Intelligence, amounting to 27. When viewed on the N-Gain criteria, the experimental class with the Intelligence model entered the ineffective criteria. The experimental class with the problem-based learning model is in the criteria of being quite effective, while the control class with the conventional model is in the less effective criteria.